A scheme to improve the coupling efficiency and working distance between laser diode and single mode fiber - Rahman,, FA; Teik,, CH; Takahashi,, K (2002)
A new scheme is proposed for a hemispherical lensed fiber having a high coupling efficiency and a long working distance between the laser diode (LD) and the single mode fiber (SMF). An analytical approach based on the theory of Gaussian beam propagation is used to predict the coupling efficiency. The measured coupling efficiency for a LD operating at a wavelength of 1.31 mum is as high as 55%, with a working distance of 65 mum and these values are close to the predicted one. (C) 2002 Elsevier Science B.V. All rights reserved.